Effect of religious fatalism and concern about new variants on the acceptance of COVID-19 vaccines - Mamani-Benito, Oscar; Farfán-Solís, Rosa; Huayta-Meza, Mariné; Tito-Betancur, Madona; Morales-García, Wilter C.; Tarqui, Edison Effer Apaza (Frontiers in Psychiatry, 2023)
Introduction: To protect public health, it is important that the population be vaccinated against COVID-19; however, certain factors can affect vaccine acceptance. Objective: The objective of this study was to determine whether religious fatalism and concern about new variants have a significant effect on the acceptance of COVID-19 vaccines. Methodology: An explanatory study was conducted with 403 adults of legal age captured through non probabilistic convenience sampling in vaccination centers in the 13 health networks of the Regional Health Directorate of Puno, Peru. Data were collected through a brief scale of religious fatalism, a scale of acceptance of vaccines against COVID-19 and a scale of concern about a new variant of COVID-19. Results: The proposed model obtained an adequate fit. There was a negative effect of religious fatalism on vaccine acceptance, a positive effect of fatalism on vaccine rejection, a positive effect of concern about new variants on the acceptance of vaccines, and a positive effect of concern about new variants on vaccine rejection. Conclusions: These findings provide evidence for the usefulness of considering both religious fatalism and concern about new variants affect the intention to receive the COVID-19 vaccine in adults in southern Peru.